The Social Flood Pulse and socio-ecological Transformation of the Tonle Sap - Sithirith, Mak; Carl, Grundy-Warr (Wiley, 2025)
The flood pulse is a hydrological concept of the river-lake-floodplain system, demonstrating the varying hydrological regimes between wet and dry seasons, which drive productivity and interaction of living and non-living organisms in river-lake-floodplain systems (RLFS). This paper posits that the flood pulse is a ‘social,’ physical, and hydrological driver of change in the Mekong Basin, particularly for the ‘pulsing heart’ of Tonle Sap Lake (TSL). Although the flood pulse provides a comprehensive knowledge of RLFS, there has been less attention on how the flood pulse contributes to the development of river-lake society. This paper examines the social aspects of the flood pulse in RLFS and explores how communities adapt to changing hydrological regimes between the wet and dry seasons. It is argued that the physical and social dimensions of the flood pulse should be essential considerations in water governance, environmental and social policy arenas. It concludes that the flood pulse shapes human settlements in TSL into water-based, water-land-based, and land-based communities, induces vertical and horizontal mobilities of communities between the wet and dry seasons, and influences the organization of productive spaces and non-spatial activities to sustain livelihoods. Developments such as hydropower are causing ecological and social transformations in TSL.